Membangun Fondasi Pendidikan Berkualitas Melalui Sistem Administrasi Pendidikan Islam - Muhamad Iqbal; Muhammad Badruzzaman; Abdul Malik; Iman Sopyan; Adi Rosadi (CV Edujavare Publishing, 2024)
The Madrasah [Sunanul Huda], as an Islamic educational institution committed to Islamic teachings, faces increasingly complex challenges in managing Islamic education in the contemporary era. Islamic education institution Sunanul Huda as an educational institution belonging to the Islamic school has a major challenge in managing Islamic education as an Islamic educational institution. This paper discusses the main concepts, components, challenges, as well as strategies for developing the system of administration of Islamic education in Madrasah Sunanul Huda. This paper is written based on descriptions and analyses. The result is that the administration of Islamic education in Islamic educational institution Sunanul Huda covers six components which include curriculum, human resource, school education, character education and morals, organizing, controlling, evaluating, and cooperating with parents and the surrounding community. The major issues faced in the establishment of the Islamic education administration system include limited human resources, changes in the dynamics of education that require changes, and limited space and facilities. To address these challenges, Madrasah [Sunanul Huda] strengthens teacher training and development programs, enhances the Islamic education curriculum, and expands partnerships with parents and the community. Through a profound understanding and robust implementation of the Islamic education administration system, Madrasah [Sunanul Huda] can build a foundation of quality education that is relevant and in line with Islamic teachings, while significantly contributing to the formation of students'faith and noble character.